KONSTRUKSI STRUKTUR TIGA DIMENSI FITOESTROGEN HASIL KONVERSI DARI SMILES STRING REPRESENTATIONS UNTUK SIMULASI PENAMBATAN MOLEKULER MENGGUNAKAN SOFTWARE PLANTS - Enade Perdana Istyastono; Nunung Yuniarti (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Phytoestrogens have some important biological effects and could be employed as medicinal resources, for example as cancer chemopreventive agents. Phytoestrogen is defined as a phytochemical that has estrogenic or anti estrogenic effects. However, there is no database providing comprehensive list of phytoestrogen structures. In computer-aided drug discovery, the database is required to perform virtual screening for retrospective validation and structure-based drug design. The research presented in this article attempted to collect a comprehensive list of phytoestrogen structures. Subsequently, the structures were prepared in their three dimensional structures using SPORES1.3 for molecular docking simulations using PLANTS1.2. The ready-to-dock structures were then stored online as phytoestrogens.zip and could be downloaded from http://molmod.org/phytoestrogens.zip. This database contains 30 ready-to-dock unique phytoestrogens with total of 53 different configurations.